(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Staphylococcus aureus is a ubiquitous bacterium that is generating increasingly bad press coverage due to its propensity to adopt a pathogenic lifestyle in hospital and community settings. Lipases catalyze both the hydrolysis and synthesis of triacylglycerols. Many of these enzymes are characterized by stability at high temperatures and in organic solvents. Objective:Purification of the enzyme by using the conventional methods and characterization of lipase. Methods:Purification included: extraction of the enzyme, the precipitation of the enzyme by ammonium sulphate, dialysis, ionic exchange chromatography by using DEAE-Cellulose (Diethylaminoethyl-Cellulose), and gel filtration by using Sephacryl S-200. Equal amounts of purified lipase solution were mixed with PBS (Phosphate buffer sodium) solutions of different pH (4,5,... until 10) and incubated in a water bath at 37 oC for 30 minutes, then the lipase activity was estimated. The purified lipase was incubated at different degrees of temperature (5, 15, ...until 85 oC) for 30 minutes. The molecular weight was determined by gel filtration chromatography. Results:The results revealed that the crude enzyme solution had a total protein concentration of 21.3 mg/ml and an enzyme activity of 257 µmole/ml. The lipase was precipitated by ammonium sulphate with 50-75%. Then the protein concentration was 4.7 mg/ml while the enzyme activity was 812 µmole/ml. Revealed that the protein concentration was 2.3 mg/ml and enzyme activity was 1020 µmole/ml. This revealed that the protein concentration was 0.9 mg/ml and the enzyme activity was 1669 µmole/ml. Conclusion: Lipase was purified to a considerable homogeneity and the characterization experiments revealed that the enzyme showed considerable heat stability and was optimally active at alkaline pH. Key words: Lipase, ion exchange chromatography, gel filtration chromatography, molecular weight.